Ganetespib, an HSP90 inhibitor, kills Epstein–Barr virus (EBV)-infected B and T cells and reduces the percentage of EBV-infected cells in the blood. Issue 4 (3rd April 2017) - Shatzer, Amber; Ali, Mir A.; Chavez, Mayra; Dowdell, Kennichi; Lee, Min-Jung; Tomita, Yusuke; El-Hariry, Iman; Trepel, Jane B.; Proia, David A.; Cohen, Jeffrey I.
Abstract: HSP90 inhibitors have been shown to kill Epstein–Barr virus (EBV)-infected cells by reducing the level of EBV EBNA-1 and/or LMP1. We treated virus-infected cells with ganetespib, an HSP90 inhibitor currently being evaluated in multiple clinical trials for cancer and found that the drug killed EBV-positive B and T cells and reduced the level of both EBV EBNA-1 and LMP1. Treatment of cells with ganetespib also reduced the level of pAkt. Ganetespib delayed the onset of EBV-positive lymphomas and prolonged survival in SCID mice inoculated with one EBV-transformed B-cell line, but not another B-cell line. The former cell line showed lower levels of EBNA-1 after treatment with ganetespib in vitro . Treatment of a patient with T-cell chronic active EBV with ganetespib reduced the percentage of EBV-positive cells in the peripheral blood. These data indicate that HSP90 inhibitors may have a role in the therapy of certain EBV-associated diseases.